PENENTUAN PRODUK RADAR CUACA PALING TEPAT UNTUK MEMBUAT PERINGATAN DINI CUACA EKSTRIM DENGAN MENGGUNAKAN METODE ANALYTICAL HIERARCY PROCESS (AHP) - Sumaja, Kadek; Suarbawa, Komang Ngurah; Irmawan, Decky (BULETIN FISIKA; Vol 16 No 1 (2015): BULETIN FISIKA, 2015)
To solve the problem of determining the most appropriate products RADAR weather to make early warning of extreme weather that is efficient, effective, fast and precise then used method of Analytical Hierarcy Process (AHP). Analytical Hierarchy Process (AHP), which is a decision support system developed by Thomas L. Saaty. Using this method could be determined by the priority of multiple criteria analysis with pairwise comparisons (Pairwise Comparison) of each criteria and alternatives that have been determined. Prioritization is done by using the eigenvectors of the iteration of the squares of the pairwise comparison matrix. Consistency test will be performed on the data obtained to determine the feasibility of the data so the data can be used for prioritization of comparison criteria, comparison of alternatives and determination of the best alternative that will determine the priority value of the product weather RADAR to make early warning of extreme weather. From the results obtained by the determination of the best alternative, PPI products have the highest weights, followed by the product CMAX, then the product UWT and the final is product TRACK.  Keywords: weather RADAR , AHP , eigenvectors